Controllable synthesis of an intercalated ZIF-67/EG structure for the detection of ultratrace Cd2+, Cu2+, Hg2+ and Pb2+ ions - Ma, Laifeng; Zhang, Xueyi; Ikram, Muhammad; Ullah, Mohib; Wu, Hongyuan; Shi, Keying (Chemical engineering journal (Lausanne, Switzerland : 1996), 2020)
Controllable synthesis of ZIF-67/EG intercalated structure for detection of ultra-trace Cd2+, Cu2+, Hg2+ and Pb2+ ions. [Display omitted] •Controllable synthesized and characterized an intercalated ZIF-67/EG as HMI sensor.•Ultratrace detection of Cd2+, Pb2+, Cu2+ and Hg2+ by reliable SWASV method.•ZIF-67/EG sensor exhibits high sensitivity and low detection limit.•ZIF-67/EG sensor enables detect HMIs simultaneously or selectively.•Effective cationic MOF sensor for environmental fields. The fabricated intercalated structure composed of a Co-based zeolitic imidazolate framework (ZIF-67) and expanded graphite (EG) has been prepared using a facile and simple one-pot hydrothermal reaction. This framework was used to detect heavy metal ions (HMIs) via a square wave anodic stripping voltammetry (SWASV) method for the first time. Here, the composite material is useful for the selective electrochemical detection of nanomolar Cd2+, Pb2+, Cu2+ and Hg2+ in aqueous solutions simultaneously or individually. The operational parameters such as pH, electrolyte, deposition potential, and deposition time were optimized to detect various HMIs. The electrochemical properties and applications of the modified electrode were also studied. The constructed electrochemical sensor displays good performance with a large electrochemically active surface areas, high sensitivity and low limit of detection (LOD). These impressive features originate from the synergistic effects of ZIF-67 and EG. This study proposes a new strategy for heavy metal ion detection using a novel morphology of a metal–organic framework (MOF) composite.